De la innovación docente universitaria a su transferencia a la escuela: una experiencia educativa desde la perspectiva de género (Experiencias) - Morón Monge, Hortensia (2022)
Based on a teaching innovation project at the University of Seville (Spain), an itinerant exhibition about women´s contribution to science was designed. This exhibition was exposed in different schools of Seville, accompanied by workshops and talks to bring university research closer to schools. In this work, one of these experiences with primary school children is presented, where discussions, open interviews, experimental activities, etc., were implemented to improve the perceptions of science from a feminist perspective and thus promote scientific careers among girls.